2022
DOI: 10.3390/nano12111937
|View full text |Cite
|
Sign up to set email alerts
|

Promising Colloidal Rhenium Disulfide Nanosheets: Preparation and Applications for In Vivo Breast Cancer Therapy

Abstract: Photothermal therapy (PTT) has become an important therapeutic strategy in the treatment of cancer. However, exploring novel photothermal nanomaterials with satisfactory biocompatibility, high photothermal conversion efficiency, and efficient theranostic outcomes, remains a major challenge for satisfying clinical application. In this study, poly-ethylene glycol modified rhenium disulfide (PEG-ReS2) nanosheets are constructed by a simple-liquid phase exfoliation method. The PEG-ReS2 nanosheets were demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…In addition, the results of the photothermal agent combined with RT showed that the photothermal agent could significantly improve the hypoxic environment of tumors, thus reducing the RT resistance of tumors and finally achieving significant therapeutic effects. Song et al [ 134 ] also synthesized PEG-ReS 2 nanosheets with different methods, which also have ideal photothermal conversion efficiency and could effectively ablate tumors. In addition, the micro-RNA (miRNA) expression analysis and evaluation methods also showed that PEG-ReS 2 nanotablets had good therapeutic effects ( Figure 8 d).…”
Section: Study On Re In Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the results of the photothermal agent combined with RT showed that the photothermal agent could significantly improve the hypoxic environment of tumors, thus reducing the RT resistance of tumors and finally achieving significant therapeutic effects. Song et al [ 134 ] also synthesized PEG-ReS 2 nanosheets with different methods, which also have ideal photothermal conversion efficiency and could effectively ablate tumors. In addition, the micro-RNA (miRNA) expression analysis and evaluation methods also showed that PEG-ReS 2 nanotablets had good therapeutic effects ( Figure 8 d).…”
Section: Study On Re In Cancer Therapymentioning
confidence: 99%
“…[ 135 ], Copyright 2011, Royal Society of Chemistry); ( d ) schematic illustration of PEG−ReS 2 nanosheets employed for in vivo breast cancer therapy study (reproduced with permission from Ref. [ 134 ], Copyright 2022, MDPI). NCs, nanoclusters; PVP, polyvinyl pyrrolidone; CT, computed tomography; PA, photoacoustic imaging; PEG, polyethylene glycol.…”
Section: Figurementioning
confidence: 99%